Analisis Kritik Sastra Feminis terhadap Cerpen Aku Perempuan Karya Muh Fiqrawal Rahman - Diana Wati Sinaga (JURNAL ILMIAH NUSANTARA, 2026)
This research aims to reveal the forms of feminist literary criticism contained in the short story Aku Perempuan by Muh. Fiqrawal Rahman. The focus of the study is directed at the representation of female figures and gender relations which show injustice towards women in various social spaces, especially educational spaces. This research uses a descriptive qualitative approach with literary text analysis methods. The research data is in the form of words, phrases, sentences and paragraphs in short stories which contain elements of marginalization, subordination, stereotypes, as well as women's experiences of violence and resistance. Data collection techniques were carried out using the reading and note-taking method, while data analysis was carried out descriptively-interpretatively using a feminist literary criticism perspective. The research results show that the short story Aku Perempuan represents systemic gender injustice through depictions of sexual harassment, the silencing of women's voices, and unequal power relations between women and institutional authorities. Women are depicted as subjects who experience psychological trauma, lose their safe space, and are forced to adapt to a patriarchal system that ignores the rights and experiences of victims. This short story not only records the personal experiences of female characters, but also conveys social criticism of the patriarchal structure which is still deeply rooted in educational institutions.